Spatial variability of physical attributes of the soil in amazonian black soil under coffee cultivation - Cardoso Mota Júnior, Pedro; Costa Campos, Milton Cesar; Campos Mantovanelli, Bruno; Franciscon, Uilson; da Cunha, José Mauricio (Coffee Science - ISSN 1984-3909, 2017)
The conversion of natural ecosystems into agricultural systems causes significant changes in soil properties associated with the growing deforestation in the Amazon region influencing the destabilization of the ecosystem. Thus, it is aimed with this study was to evaluate the spatial variability of physical attributes of the soil in black Indian land area (ICC) under Conilon coffee cultivation. It was marked a sampling grid with dimensions of 88 × 64 m, with regular spacing of 8 m, for a total of 88 sampling points, structured and undisturbed soil samples were collected in layers of 0.00 to 0.05; 0.05-0.10; 0.10-0.20 and 0.20-0.30 m. We conducted the following physical analysis: particle size, aggregate stability, total organic carbon (TOC), carbon stock (EstC), macroporosity (MAP), microporosity (MiP), bulk density (Ds), total porosity (PT), soil penetration resistance (RP) and volumetric water content (θ). The results were submitted to descriptive statistical and geostatistical analysis. The ICC’s exhibit great potential that can support the increase in production, since they have excellent soil condition that refers to physical attributes, and evaluated in these layers exhibited no constraint and hindrance to the root culture.